Gender assessment for women’s economic empowerment in Doyogena climate-smart landscape in Southern Ethiopia - Ambaw, Gebermedihin; Tadesse, Meron; Mungai, Catherine; Kuma, Simegn; Radeny, Maren A.O.; Tamene, Lulseged D.; Solomon, Dawit (2019)
Agricultural production systems in Ethiopia depend on seasonal rains, which are increasingly becoming variable, affecting the livelihoods of many farmers. Women in rural areas are more vulnerable to climate change and climaterelated risks due to existing social norms and gender inequalities (limited ownership and control over productive assets/resources, decision-making power, access to information, extension services, market etc.) and multidimensional social factors. These gender inequalities affect the ability of women to adapt to climate change. On the other hand, women have unique knowledge and skills that can help create effective and sustainable responses to climate change (Habtezion 2013).